(untitled) (Proceedings of International Conference on Special Education, 2017)
High-ability students from low-income and/or minority backgrounds are generally unidentified and underrepresented in gifted programs (Frasier, 1987, as cited in Frasier, 1989). But even when these children are able to access gifted programs, many obstacles stand in the way of achieving their potential (Beck, 2011). In 2014, the poverty incidence in the Philippines was pegged at 25.8 percent. About 10.5 percent of its citizens had incomes below the food threshold during the first quarter of 2014 (Philippine Statistics Authority, 2015). For many years, affluent colleges and universities in the country have been providing high- ability students from low socio-economic backgrounds the opportunity to access quality tertiary education through financial scholarships. A qualitative study was conducted in 2016 involving three (3) full financial scholars to an affluent women’s college. Graduates of public high schools, they were recognized by their college for their academic achievements and/or leadership skills. The study examined (a) the challenges they encountered while maintaining financial scholarship, (b) their responses to those challenges, and (c) their support providers. Content analysis of personal interviews revealed that the participants were confronted by various overlapping challenges concerning their home, emotions, maintenance of financial scholarship, and lack of finances. Overcoming these while maintaining high academic performance required motivation, self-management and spirituality. They credited the support of their family and friends, God, the scholarship administrators, and their teachers. Recommendations to help high ability students from low socio-economic backgrounds overcome diverse challenges and maintain high academic performance in an affluent college are provided.